Regional centennial precipitation variability over Germany from extended observation records. (22nd August 2012) - Brienen, Susanne; Kapala, Alice; Mächel, Hermann; Simmer, Clemens
ABSTRACT The data base of daily precipitation over Germany has been recently extended by digitizing additional historical hand‐written observations. The extension from 65 to 118 stations has increased the density of the available station network to a degree which allows both meaningful regional analyses and less error‐prone trend and return level estimates. In this article first results of the examination of the precipitation behaviour in the winter and summer season throughout the entire 20th century are presented. To assess the spatial scale of similarities or spatial coherence of several precipitation indices from the 118 stations, Principal Component Analysis is used. The extracted leading patterns (six in winter, nine in summer) resemble nicely regions of different geographical characteristics and prevailing wind directions which puts some credibility on the quality of the newly digitized observations. The long‐term linear trends of the regionally averaged time series differ substantially between precipitation indices, regions, seasons, and sub‐periods. For the whole century, significant increases are found for most of the intensity‐related indices in the Southern part of the country in winter and in some of those indices in the Rhineland/Sauerland and Alpine regions in summer. The two halves of the 20th century, are, however, characterized by partly opposite trends in the precipitation indices, and different regions are affected by these changes. An analysis of trend robustness by means of 30‐year moving trends indicates a low stability of the trends during the 20th century, which is partly caused by interdecadal variability of the precipitation characteristics. For 100‐year return levels, changes between the estimates obtained from the entire century and from the first and second 50 years differ in particular in the extent of their confidence intervals. In consequence, the availability of long precipitation records is very important for practical applications, and further extension of data records is recommended.